Autophagy-mediated clearance of ubiquitinated mutant huntingtin by graphene oxide. Issue 44 (28th October 2016) - Jin, Peipei; Wei, Pengfei; Zhang, Yunjiao; Lin, Jun; Sha, Rui; Hu, Yi; Zhang, Jiqian; Zhou, Wei; Yao, Han; Ren, Li; Yang, James Y.; Liu, Yanchun; et al.
Abstract : Many of the neurodegenerative disorders such as Huntington's disease (HD) are caused by the accumulation of intracytoplasmic aggregate-prone proteins. Abstract : Many of the neurodegenerative disorders such as Huntington's disease (HD) are caused by the accumulation of intracytoplasmic aggregate-prone proteins. These toxic protein aggregates are mainly degraded by autophagy, thus elevating the autophagy level to enhance the degradation of these proteins representing an emerging viable approach for the treatment of neurodegenerative diseases. In this report we showed that graphene oxide (GO), an engineered nanomaterial with enormous potential in biomedical applications, effectively enhanced the clearance of mutant huntingtin (Htt), the aggregate-prone protein underlying the pathogenesis of HD. This enhancing effect of GO was autophagy-mediated, as blocking autophagy by chemical inhibitors at either the autophagosome formation stage or the autophagosome–lysosome fusion stage, or more specifically by knocking-down an essential autophagy gene, led to a significant reduction in the ability of GO to elicit Htt degradation. Interestingly, the autophagy induced by GO had the normal capacity to degrade its cargo including LC3-II and Htt, but not p62/SQSTM1 (p62), and was dependent on the activation of class III phosphatidylinositol 3-kinase (PtdIns3K) and MEK/ERK1/2 signaling pathways, without mTOR involvement. GO also increased ubiquitination of Htt, an event necessary for Htt's clearance. Furthermore, ubiquitinated huntingtin protein preferentially binds to GO, and abundant GO was found in autophagosomes and autolysosomes, thus raising the possibility that GO may directly deliver the bound protein to autophagosomes for degradation. Our results revealed a novel biological function of GO and may have implications for developing nanomaterial-based therapeutics for neurodegenerative diseases.